Changes of Health Related Quality of Life Dimensions In Hemodialysis Patients - Wantonoro Wantonoro; Arida Rahmawati (Universitas Muhammadiyah Semarang, 2020)
Hemodialysis procedure was influenced by the patient's quality of life. Comprehensive understanding changes of health-related quality of life dimensions to provide the best nursing care planning is needed. This study aimed to determine longitudinal changes for each dimension of health-related quality of life patient who received hemodialysis. Longitudinal study and Generalized estimating equations Statistic analysis were used. Thirty respondents were included in this study between December 2019 and July 2020. Overall trend each dimension of health-related quality of life in hemodialysis patients were decreased. Interestingly, a social function was showed potential to be maintained and improved. Also, age, co-morbidities and education level were found as predictors some of the changes the health-related quality of life dimensions. Developing nursing included social and family care program intervention to maintenance psychological dimensions is recommended for future study.